Proyecto de factibilidad para la implementación de un burger en el aeropuerto “Camilo Ponce Enríquez” de la provincia de Loja - Castro Gallego, Segundo Lizardo (2015)
This research work, fundamental objective is to implement a fast food(Burger) site at the airport "Camilo Ponce Enríquez of the province of Loja. The methodology used for the achievement of the objectives, makes inductive and deductive methods reference, as well as the techniques of interviews and surveys, that through instruments as the interview guide and the questionnaire allowed for the study of applied market information, for the technical study is considered unsatisfied demand and requirement of the productive process. In market research , segmentation is performed considering users of air transport services in the province of Loja as the study population and a sample of 399 surveys were obtained , based on these data we have determined the potential demand for 123276 the actual demand for 63339 , per capita annual consumption of 12.01 and effective demand projected 738400 . Likewise the technical study, described the process used for the development of fast foods, as well as determined the installed capacity of 50.520 burgers and salchipapas 172.800. The organizational administrative study is established the levels existing in the company, as well as the leaves of functions for each of the employees, with the aim of what the company can function better and efficiently at the stage of production. Within the economic and financial study determined a total initial investment of $ 19.683,72. On the financial evaluation was determined their feasibility through indexes as the VAN is $105.438,64,, the TIR with a value of 89,19%, the Capital recovery period of 7 months and 9 days, a benefit of 0.35 cents per each dollar invested; and, the sensitivity analysis with a rise in cost of 28,68%, and analysis with decrease in revenues of 21,24% Within the conclusions which were reached after having developed this work, is that it is feasible to develop it through the presentation and analysis of results, so it is recommended to run it